THERMOPHYSICAL AND THERMAL CHARGING ENHANCEMENT OF PEG/Al₂O₃ COMPOSITES FOR THERMAL ENERGY STORAGE (TES) - Amdy Fachredzy; Chyntia R. Situmorang; Erna Frida; Ariadne L. Juwono; Anggito P. Tetuko; Muhammad Fauzi; Muhammad A. H. Nabawi; Achmad Maulana S. Sebayang; Eko A. Setiadi (Indonesian Physical Review, 2026)
The transition to renewable energy continues to face challenges in balancing supply and demand. Thermal Energy Storage (TES) based on Phase Change Materials (PCM) offers a potential solution, with polyethylene glycol (PEG) providing high storage capacity but low thermal conductivity. This study focuses on enhancing the performance of PEG 6000 by incorporating aluminum oxide (Al₂O₃, 8 and 12 wt.%) and sodium dodecyl benzene sulfonate (SDBS) as a surfactant. X-ray Diffraction (XRD) confirmed that no new phases were formed, while Differential Scanning Calorimetry (DSC) recorded an increase in latent heat up to 224.6 J/g for PEG/Al₂O₃ 12%. Thermal conductivity improved by more than 33.3%, and Thermogravimetric Analysis (TGA) verified enhanced thermal stability. Charging–discharging tests further demonstrated an extended average charging time with slight fluctuations during discharging. These findings highlight the promising potential of PEG/Al₂O₃ composites for TES applications in renewable energy systems.